The Benefit Principle in Determining Compensation for Real Estate Expropriation - Trembecka, Anna (Geomatics and Environmental Engineering, 2023)
Polish expropriation law introduces a compensation system based on the socalled “benefit principle”. This principle assumes estimating the value of the property based on its intended use if it results in a greater value. The problem of considering the intended purpose of expropriation and, consequently, the application of the benefit principle is widespread in compensation proceedings relating to road investments. The research objective of this paper is an attempt to answer the question of whether the benefit principle should be maintained in the real estate appraisal procedure in order to determine compensation, i.e. whether the intended use resulting from the purpose of expropriation should be taken into account if it increases its value. The research also focuses on identifying those factors that should be considered instead of the benefit principle in order to estimate fair compensation for expropriated real estate. Part of the study is also devoted to the assessment of planned changes in legal regulations regarding compensation proceedings. The subject of the research are procedures and regulations for determining compensation for real estate expropriated for road investments in Poland. The analysis covers the stages of the compensation procedure and the factors affecting the amount of compensation. These procedures were compared with those in force in other countries in the context of applying the benefit principle. The results of the analysis lead to the conclusion that the amount of compensation should be independent of the intended purpose of expropriation. This is because planning classification for public purposes cannot be treated as a criterion which increases the market value of the expropriated property.